The contribution of CYP2C gene subfamily involved in epoxygenase pathway of arachidonic acids metabolism to hypertension susceptibility in Russian population. (19th May 2017) - Polonikov, Alexey; Bykanova, Marina; Ponomarenko, Irina; Sirotina, Svetlana; Bocharova, Anna; Vagaytseva, Kseniya; Stepanov, Vadim; Churnosov, Mikhail; Bushueva, Olga; Solodilova, Maria; Shvetsov, Yaroslav; Ivanov, Vladimir
ABSTRACT: Numerous studies demonstrated an importance of cytochrome P-450 epoxygenase pathway of arachidonic acids metabolism for the pathogenesis of essential hypertension (EH). The present study was designed to investigate whether common single-nucleotide polymorphisms (SNP) of CYP2C gene subfamily such as CYP2C8 (rs7909236 and rs1934953), CYP2C9 (rs9332242), and CYP2C19 (rs4244285) are associated with susceptibility to EH in Russian population. A total of 816 unrelated Russian individuals comprising 425 EH patients and 391 normotensive controls were included into the study. Genotyping of SNPs was performed using the MassARRAY 4 system. SNP rs7909236 of CYP2C8 was significantly associated with increased risk of EH (OR adjusted for sex and age was 2.99 95% CI 1.39-6.44, P = 0.005). SNPs rs1934953 CYP2C8 and rs4244285 of CYP2C19 showed association with EH risk but at a borderline statistical significance ( P ≤ 0.04). Combination of genotypes CYP2C8 rs7909236 TT and CYP2C19 rs4244285 GG was associated with increased EH risk (OR 3.34 95%CI 1.48-7.51, P = 0.004). Genotype–phenotype correlation analysis showed that the levels of CYP2C8 mRNA were significantly correlated with SNP rs7909236 ( P = 0.01). in silico functional prediction analysis revealed the functionality of majority of investigated SNPs. Thus, genes of CYP2C subfamily are important genetic determinants of susceptibility to essential hypertension in Russians.